Applying the Hierarchical Gray Relational Clustering Method to Municipal Water Use in Turkey - Gunes, Mehmet Samil; Parim, Coskun; Yildiz, Dogan; Buyuklu, Ali Hakan (TURKISH CHAMBER CIVIL ENGINEERS, 2022)
This study aims to compare the municipal water distribution performance and classify the municipal water distribution systems in the provinces of Turkey using the Gray Relational Hierarchical clustering method for both 2006 and 2016. A correlation analysis was used to determine the variables affecting the distributed water. The Hierarchical gray clusters and the changes during the decade are presented with spatial distribution maps using statistically significant variables. Consequently, the findings reveal that the municipalities of Istanbul, Izmir, Bursa, Gaziantep, and Kocaeli managed water distribution effectively, whereas the municipalities of Konya, Sanliurfa, Diyarbakir, Samsun, Trabzon, and Sakarya managed it poorly.
Keywords: Climate change; municipal water use; water management; sustainability; CONSUMPTION; Engineering